Advances in Water Purification Techniques Meeting the Needs of Developed and Developing Countries - Ahuja, Satinder; Ahuja, Satinder (Elsevier Science, 2018)
Advances in Water Purification Techniques: Meeting the Needs of Developed and Developing Countries provides a variety of approaches to water purification that can help assist readers with their research and applications. Water contamination problems occur frequently worldwide, hence the most updated knowledge on water purification systems can be helpful in employing the right type of filter or other mechanism of decontamination. The problems with arsenic contamination of water in Bangladesh and the lead problem in Flint, Michigan remind us of the need to monitor water pollution rigorously, from both point and non-point sources. - Provides a valuable resource on how to solve water contamination problems or develop new approaches to water purification - Presents advanced methods for monitoring water contamination - Describes various approaches to water purification - Encourages new developments in water purification techniques - Includes methods for assessing and monitoring environmental contaminants - Covers recent advancement in molecular techniques